2016
DOI: 10.1002/jsfa.7911
|View full text |Cite
|
Sign up to set email alerts
|

Carbon footprint as an instrument for enhancing food quality: overview of the wine, olive oil and cereals sectors

Abstract: The quantification of greenhouse gases (GHG) emissions represents a critical issue for the future development of agro-food produces. Consumers' behaviour could play an important role in requiring environmental performance as an essential element for food quality. Nowadays, the carbon footprint (CFP) is a tool used worldwide by agro-food industries to communicate environmental information. This paper aims to investigate the role that CFP could have in consumers' choices in three significant agro-food sectors in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 72 publications
(166 reference statements)
0
20
0
Order By: Relevance
“…With the intention to relate the impact of the analysis method to the olive oil product, Pattara et al [40] helped to identify a medium value with which correlate the impact of the analyses. Considering (i) an average of 13.32 kg of CO 2 eq per liter of olive oil produced and packaged (from the farm to the disposal), (ii) 5.82 kg of CO 2 eq derived from the chemical analyses performed on olive oil samples, and (iii) 0.14 kg of CO 2 eq derived from the optical analyses, this shows the high importance of the size of the chosen sample of olive oil.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…With the intention to relate the impact of the analysis method to the olive oil product, Pattara et al [40] helped to identify a medium value with which correlate the impact of the analyses. Considering (i) an average of 13.32 kg of CO 2 eq per liter of olive oil produced and packaged (from the farm to the disposal), (ii) 5.82 kg of CO 2 eq derived from the chemical analyses performed on olive oil samples, and (iii) 0.14 kg of CO 2 eq derived from the optical analyses, this shows the high importance of the size of the chosen sample of olive oil.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Other studies considered only specific indicators, especially the carbon footprint (CF) and the water footprints (WF) [28][29][30]. Extensive reviews on the application of the carbon footprint concept to wine production can be found in the literature [32][33][34][35]. Both indicators are directly linked to various key aspects of wine production such as energy consumption, land management and transportation related to the CF, and water usage for the WF.…”
Section: Introductionmentioning
confidence: 99%
“…Bosco et al (2011) concluded that the planting of vine trees and trellis systems contributed significantly to the GHG emissions when the system starts from scratch. Additionally, intensive production practices tend to produce larger amounts of GHG [22,24,25]. Mitigation strategies for GHG emissions from viticulture production can be identified by inventorying and reporting the PCF through LCA, taking into consideration emissions, material, and energy inputs [24,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, intensive production practices tend to produce larger amounts of GHG [22,24,25]. Mitigation strategies for GHG emissions from viticulture production can be identified by inventorying and reporting the PCF through LCA, taking into consideration emissions, material, and energy inputs [24,26,27]. Previous research has established that organic fertilization leads to substantial savings in GHG emissions [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation